Assessment of Online Fish Marketing in Ernakulam District, Kerala - Shyam S. Salim; Harsha Elizabeth James; N. R. Athira; R. X. Smitha; A. M. Shinu and Mohammed Meharoof 1 (Asian Journal of Agricultural Extension, Economics & Sociology, 2018)
The growth of fish production and development of fishery sector is highly dependent on an efficient fish marketing system. Fish marketing strategies developed and evolved along with the changing time and has now reached the digital era where the possibilities of incorporating technology in the marketing system is being explored. Online fish marketing is the new innovative approach in the field, trying to cater to the ever-increasing demand of high quality fresh and affordable fish among the consumers delivered within the shortest time period. On one hand, it helps the producers get a deserving legitimate share in the consumer's rupee and on the other hand, it safeguards consumer's rights against excessive prices. This study is an attempt to assess the online fish trade existing in Ernakulam district of Kerala. Seventeen firms/outlets were selected to analyse various aspects related to the online firms including species traded, mode of sales, customer profile, storage facilities, constraints faced etc. Results reveal that all the online fish trading firms were of recent origin and their average monthly turnover was 10 lakhs. Firms with wider outreach or strong backward and forward linkages were found to realize much higher returns when compared to others. Around 31 percent of the online fish trading firms opined that customers opt their service because of the reason that they can save their time. Twenty-four percent of them reported that readiness of the product traded online attracted their customers to choose their services. Many of the firms were found to have closed their outlets due to many constraints faced by them. Huge overheads/advertisement costs were mentioned as the major constraint faced by the online trading firms. When considering fish marketing in the Ernakulam district, only 0.52% of the total fish marketed is being delivered by the online firms.